Or see self-efficacy in personal finance decision (Research, Society and Development, 2022)
The objective is to identify how the self-efficacy bias influences the decision-making process in terms of personal financial investments. The analysis was performed using a linear regression model and the OLS method. Self-confidence can lead to less rational decision-making due to the underestimation of concrete facts, harming the investor's performance. As for the profitability of investments in the last year, 63% stated that they had a good gain in the last year, a high belief in self-efficacy to act and make financial decisions.